2006
DOI: 10.1002/jor.20210
|View full text |Cite
|
Sign up to set email alerts
|

Strain and excursion of the sciatic, tibial, and plantar nerves during a modified straight leg raising test

Abstract: A modified straight leg raising (SLR) in which ankle dorsiflexion is performed before hip flexion has been suggested to diagnose distal neuropathies such as tarsal tunnel syndrome. This study evaluates the clinical hypothesis that strain in the nerves around the ankle and foot caused by ankle dorsiflexion can be further increased with hip flexion. Linear displacement transducers were inserted into the sciatic, tibial, and plantar nerves and plantar fascia of eight embalmed cadavers to measure strain during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 32 publications
(38 reference statements)
10
111
1
3
Order By: Relevance
“…23 secondary ICD-10 codes and conditions associated with heel pain are G57.5 Tarsal tunnel syndrome and G57.6 Lesion of plantar nerve 23 Plantar fascial fibromatosis/Contracture of plantar fascia, -ate pathology of the plantar fascia, plantar nerves near the proximal plantar fascia, or tissues of the tarsal tunnel, are often overlapping because it is difficult to selectively load the tissues hypothesized to be the source of a patient's heel pain during physical examination 2 and treatment procedures. 11,38 fasciitis, tarsal tunnel syndrome, and plantar nerve lesions codes are b28015 Pain in lower limb and . G57.5 G57.6…”
Section: IImentioning
confidence: 99%
“…23 secondary ICD-10 codes and conditions associated with heel pain are G57.5 Tarsal tunnel syndrome and G57.6 Lesion of plantar nerve 23 Plantar fascial fibromatosis/Contracture of plantar fascia, -ate pathology of the plantar fascia, plantar nerves near the proximal plantar fascia, or tissues of the tarsal tunnel, are often overlapping because it is difficult to selectively load the tissues hypothesized to be the source of a patient's heel pain during physical examination 2 and treatment procedures. 11,38 fasciitis, tarsal tunnel syndrome, and plantar nerve lesions codes are b28015 Pain in lower limb and . G57.5 G57.6…”
Section: IImentioning
confidence: 99%
“…In our study, hamstring muscle length was significantly shorter in Group 2 than in Group 1. Tightness in the posterior thigh caused by an increase in sciatic nerve tension may also reduce hip motion 5,6) . Increased sciatic nerve tension has been shown to cause ischemia and hypoxia in nerve tissue or reduce axoplasmic flow, which can induce microtrauma in an adjacent muscle 13) .…”
Section: Discussionmentioning
confidence: 99%
“…The SLR with 15 to 20 degrees of ankle dorsiflexion, a modification of the SLR, has been used to measure sciatic nerve tension regardless of hamstring muscle length 5) . We performed the SLR and the modified SLR to test sciatic nerve tension using a digital inclinometer to measure sciatic nerve tension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the knee is flexed, the nerve moves posterolateral and the nerve moves deeply into the tunnel when the knee is extended. During a straight leg raise with knee extension, the sciatic nerve experiences a proximal excursion of 28 mm medial towards the hip joint [54]. Additionally, it has been reported that neurapraxia can be produced at 6% strain and that a complete block can occur at 12% strain [55].…”
Section: Aetiology and Clinical Featuresmentioning
confidence: 99%